Multi-functional technical devices for improvement and control of athletes` preparedness in martial arts - Zadorozhna, O.; Briskin, Y.; Pityn, M.; Smyrnovskyy, S.; Semeryak, Z.; Khomiak, I.; Hlukhov, I. (SportMont, 2020)
The present work studied specifics of technical devices for the improvement and control of athletes` preparedness in martial arts. Their use is aimed at the improvement of different sides of athletes` preparedness, including technical and tactical skills, and theoretical knowledge. The main advantage of the devices is the opportunity not only to develop sports skills but also to have operational feedback between the athlete and the coach or team partner in real time. Three multi-functional technical devices were created: "TTT", "Cube", and "Device for the technical training of fencers". Their efficiency was estimated with two pedagogical experiments involving 52 young epee and foil fencers (age 11-15 years) and 45 epee fencers (age 11-15 years). The results of the first pedagogical experiments illustrated that the use of "TTT" simulator enabled increasing the sportsmen`s level of knowledge at 48.3%-145.5% (p<0.05). The results of the second pedagogical experiments illustrated that the use of "Device for the technical training of fencers" enabled increasing the sportsmen`s technical preparedness (p<0.01).